Enteroaggregative Escherichia coli in Daycare—A 1-Year Dynamic Cohort Study - Hebbelstrup Jensen, Betina; Stensvold, Christen R.; Struve, Carsten; Olsen, Katharina E. P.; Scheutz, Flemming; Boisen, Nadia; Röser, Dennis; Andreassen, Bente U.; Nielsen, Henrik V.; Schønning, Kristian; Petersen, Andreas M.; Krogfelt, Karen A. (Frontiers in Cellular and Infection Microbiology, 2016)
Enteroaggregative Escherichia coli (EAEC) has been associated with persistent diarrhea, reduced growth acceleration, and failure to thrive in children living in developing countries and with childhood diarrhea in general in industrialized countries. The clinical implications of an EAEC carrier-status in children in industrialized countries warrants clarification. To investigate the pathological significance of an EAEC carrier-state in the industrialized countries, we designed a one-year dynamic cohort study and performed follow-up every second month, where the study participants submitted a stool sample and answered a questionnaire regarding gastrointestinal symptoms and exposures. Exposures included foreign travel, consumption of antibiotics and contact with a diseased animal. In the capital area of Denmark, a total of 179 children aged 0–6 years were followed in a cohort study, in the period between 2009 and 2013. This is the first investigation of the incidence and pathological significance of EAEC in Danish children attending daycare facilities. Conventional microbiological detection of enteric pathogens was performed at Statens Serum Institut, Copenhagen, Denmark and at Hvidovre Hospital, Copenhagen, Denmark. Parents completed questionnaires regarding gastrointestinal symptoms. The EAEC strains were further characterized by serotyping, phylogenetic analysis, and susceptibility testing. EAEC was detected in 25 (14%) of the children during the observational period of one year. One or more gastrointestinal symptoms were reported from 56% of the EAEC-positive children. Diarrhea was reported in six (24%) of the EAEC positive children, but no cases of weight loss and general failure to thrive were observed. The EAEC strains detected comprised a large number of different serotypes, confirming the genetic heterogeneity of this pathotype. EAEC was highly prevalent (n = 25, 14%) in Danish children in daycare centers and was accompanied by gastrointestinal symptoms in 56% of the infected children. No serotype or phylogenetic group was specifically linked to children with disease.